Tingkat Pengetahuan Pasien Diabetes Melitus pada Pencegahan Luka Kaki Diabetes - Widyastuti; Wa Ode Sri Asnaniar; Ernasari; Rahmat Hidayat (Window of Nursing Journal, 2023)
Diabetes mellitus is a chronic disease characterized by elevated blood glucose levels and is the most common disease encountered by the wider community. The most common complication in patients with diabetes mellitus is diabetic foot ulcers. The level of knowledge in people with diabetes mellitus has an important role in preventing diabetic foot ulcers. This study aims to determine the relationship between the level of knowledge of diabetes mellitus patients on the prevention of diabetic foot ulcers at the Kassi-Kassi Public Health Center, Makassar City. The research design used in this study is a correlation design and uses a cross sectional approach. The determination of the sample was carried out by purposive sampling technique with a sample size of 43 people. The correlation test was performed using the Fisher Exact Test statistical test with a significance level of < 0.05. The results showed that there was a significant relationship between the level of knowledge and the prevention of diabetic foot ulcers (p = 0.20 < 0.05). The conclusion of this study is that there is a relationship between the level of knowledge and prevention of diabetic foot ulcers in patients with diabetes mellitus at the Kassi-Kassi Public Health Center Makassar City.